Spiritual Care in the Indonesian Healthcare System A Scoping Review - M. Agus Wahyudi; Siti Nurlaili Muhadiyatiningsih; Zaenal Muttaqin; M. Ikhwan; Tuti Hidayati (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
Spiritual care is an important component of healthcare that views patients as individuals with integrated physical, psychological, social, and spiritual needs. This study aims to map the core components of spiritual care within the Indonesian healthcare system through a scoping review approach. Literature was collected from Scopus, Sinta, PubMed, ScienceDirect, and Google Scholar databases using keywords related to spiritual care and healthcare services in Indonesia. Publications from 2015–2026 were selected based on inclusion and exclusion criteria and analyzed thematically. The findings identify six major components of spiritual care in Indonesia: patients’ spiritual needs, forms of spiritual interventions, healthcare workers’ competencies, institutional and policy support, integration into clinical services, and implementation challenges. The review demonstrates that spiritual care contributes significantly to patients’ quality of life, coping capacity, psychological well-being, and healthcare quality. However, implementation remains constrained by limited regulations, shortages of trained professionals, and the lack of systematic integration into the national healthcare system.